2016
DOI: 10.1007/s10072-016-2665-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of onabotulinumtoxinA treatment on efficacy, depression, anxiety, and disability in Turkish patients with chronic migraine

Abstract: Chronic migraine causes a serious labour loss and disability in the society and increases the risk of depression and anxiety by negatively affecting the quality of life. The purpose of this study was to investigate the effects of onabotulinumtoxinA (BoNT-A) treatment on efficacy before and after treatment in our cases with chronic migraine as well as on depression, anxiety and disability caused by migraine. According to the International Headache Classification (ICHD-III beta version), 60 adult patients who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…In terms of monthly headache frequency, headache severity, number of analgesics used and MIDAS scores our findings support the association of OnabotA therapy with rapid improvement in migraine parameters usually after the first session as reported in past studies [26, 27, 30, 5153]. …”
Section: Discussionsupporting
confidence: 90%
“…In terms of monthly headache frequency, headache severity, number of analgesics used and MIDAS scores our findings support the association of OnabotA therapy with rapid improvement in migraine parameters usually after the first session as reported in past studies [26, 27, 30, 5153]. …”
Section: Discussionsupporting
confidence: 90%
“…The rationale for the exclusion of botox, nerve blocks, and IV infusion was to ensure there would be enough attacks during the run‐in phase of the study. Due to the temporal pattern of botox treatment, in which the positive effect of the treatment shows a tendency to wane between the first and third months after the treatment, we specifically excluded those who used botox 1 month prior to enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…So the improvement in anxiety and depression symptoms may either be an effect of drugs specifically targeting these symptoms, or be an effect of improvement in headache outcome, and a different study design would be needed to approach such a relation. Anyway, addressing symptoms of anxiety and depression may be one of the keys to success, as shown in studies who specifically address it in the treatment of CM with onabotulinumtoxin‐A 50,51 . In particular, the study of Blumenfeld and colleagues 51 showed that a considerable part of subjects who showed relevant depression and anxiety at baseline significantly improved over the 108 weeks of the study (respectively, 78% of those with relevant depression and 82% of those with relevant anxiety).…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, addressing symptoms of anxiety and depression may be one of the keys to success, as shown in studies who specifically address it in the treatment of CM with onabotulinumtoxin‐A. 50 , 51 In particular, the study of Blumenfeld and colleagues 51 showed that a considerable part of subjects who showed relevant depression and anxiety at baseline significantly improved over the 108 weeks of the study (respectively, 78% of those with relevant depression and 82% of those with relevant anxiety). However, the vast majority of these patients improved by 12 weeks (respectively, 62% of those with relevant depression and 69% of those with relevant anxiety).…”
Section: Discussionmentioning
confidence: 99%